Comparative Analysis of Arabic Language Learning in Higher Education Institutions in Malaysia and Indonesia - Siregar, Amy Fitriani; Shodiq, Muhammad Ja'far; Ananda Zalfa Firdaus; Lalu Rahmat Sugiara; Dina Ayu Wulandari; Nurul Zhafirah Muslim (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to conduct a comparative analysis of Arabic language learning in higher education institutions in Malaysia and Indonesia, focusing on aspects such as curriculum, methods, technology, materials, and learning duration. The study employs a library research method with a qualitative descriptive approach to review various relevant literature sources. The analysis reveals that Arabic language learning in Malaysia is more structured, with adequate technological support and the use of Arabic as the primary medium of instruction, yet it places less emphasis on speaking skills. In contrast, learning in Indonesia focuses more on productive abilities such as speaking and writing but is less evenly distributed in terms of technology and curriculum standards. This research identifies the main challenge for Malaysia as the lack of educators proficient in teaching productive skills, while Indonesia faces challenges related to infrastructure and curriculum standardization.